Transcriptional control of IFNT expression. Issue 5 (November 2017) - Ezashi, Toshihiko; Imakawa, Kazuhiko
Abstract : Once interferon-tau (IFNT) had been identified as a type I IFN in sheep and cattle and its functions were characterized, numerous studies were conducted to elucidate the transcriptional regulation of this gene family. Transfection studies performed largely with human choriocarcinoma cell lines identified regulatory regions of the IFNT gene that appeared responsible for trophoblast-specific expression. The key finding was the recognition that the transcription factor ETS2 bound to a proximal region within the 5′UTR of a bovine IFNT and acted as a strong transactivator. Soon after other transcription factors were identified as cooperative partners. The ETS2-binding site and the nearby AP1 site enable response to intracellular signaling from maternal uterine factors. The AP1 site also serves as a GATA-binding site in one of the bovine IFNT genes. The homeobox-containing transcription factor, DLX3, augments IFNT expression combinatorially with ETS2. CDX2 has also been identified as transactivator that binds to a separate site upstream of the main ETS2 enhancer site. CDX2 participates in IFNT epigenetic regulation by modifying histone acetylation status of the gene. The IFNT downregulation at the time of the conceptus attachment to the uterine endometrium appears correlated with the increased EOMES expression and the loss of other transcription coactivators. Altogether, the studies of transcriptional control of IFNT have provided mechanistic evidence of the regulatory framework of trophoblast-specific expression and critical expression pattern for maternal recognition of pregnancy.